String-Shaped Electrodes for Aβ42 Detection Towards Early Diagnosis of Alzheimer’s Disease - Bianca Seufert; Sylvia Thomas; Arash Takshi (Chemosensors)
Alzheimer’s disease (AD) affects a significant portion of humanity’s elderly population across the globe. Recent studies have identified Amyloid-Beta 42 (Aβ42) as a key biomarker for AD. In this research, we examined the feasibility of using string-shaped electrodes to develop a potentially wearable biosensor for the early detection of AD. Two types of flexible electrochemical electrodes were fabricated using a commercial thread (25% cotton-75% polyester) and an electrospun nanofiber-based string. Decorating the strings with either gold or SiC nanoparticles, several different electrodes were tested to explore their responses to Aβ42. Our results show that the nanofiber-based electrode decorated with gold nanoparticles had the highest sensitivity of 1.71 µA/pg.cm and the best limit of detection (LoD) of 8.36 pg/mL. These findings highlight the importance of the string structure in designing highly sensitive sensors.